2012
DOI: 10.1097/mbp.0b013e32834f7125
|View full text |Cite
|
Sign up to set email alerts
|

Association of home blood pressure variability with progression of chronic kidney disease

Abstract: Day-by-day BP variability as assessed by HBP measurements had no significant association with the progression of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 29 publications
1
17
0
2
Order By: Relevance
“…Notably, the SD and CV values of HBP in the current study were almost similar to those of previous studies. 1,4,14,35,36,43 The CV values of clinic BP in our study were also almost similar to those of previous studies. 6,17,18 Third, the study population had different numbers and classes of antihypertensive drugs as well as different underlying renal diseases.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Notably, the SD and CV values of HBP in the current study were almost similar to those of previous studies. 1,4,14,35,36,43 The CV values of clinic BP in our study were also almost similar to those of previous studies. 6,17,18 Third, the study population had different numbers and classes of antihypertensive drugs as well as different underlying renal diseases.…”
Section: Discussionsupporting
confidence: 80%
“…Although few data were available regarding HBPV reproducibility, our previous study has shown a significant correlation between the BPV of HBP measurements at baseline and those during the follow-up period in CKD patients. 36,43 Therefore, some populations might have the characteristics of consistently high BPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 By contrast, a recent study reported that day-by-day BP variability, as assessed by home BP measurements, had no significant association with the progression of chronic kidney disease. 20 In line with this finding, the current study by Hoshide et al 21 of Kario's Laboratory, which was performed as a posthoc sub-analysis of the Japan Morning SurgeTarget Organ Protection (J-TOP) study, failed to find a significant association between the improvement in home BP variability and the reduction of normo-and microalbuminuria (baseline UAE mg g À1 creatine (interquartile range), 18.9 (9.1-48.5)), in spite of a significant association between home BP variability and UAE at baseline, and questioned the clinical relevance of home BP variability in the progression of albuminuria, in a range of normo-to microalbuminuria in hypertensive patients. The findings by Hoshide et al would be also consistent with a previous report from the same Kario's Laboratory showing a relatively weak association between home BP variability and albuminuria in a range of normo-to microalbuminuria, which is in contrast to the strong association that has been observed between home BP variability and cardiac hypertrophy in a cross-sectional study.…”
Section: T He Accumulated Results Of Clinical Trialsmentioning
confidence: 99%
“…47,48 Based on these findings, some authors have proposed visit-to-visit BPV in systolic BP as a novel risk factor for progression of diabetic nephropathy or development of albuminuria in patients with type 2 diabetes mellitus. 47 When focusing on CKD populations, whether or not with diabetes mellitus, several studies, but not all, 55,56 have shown increasing values of day-by-day home BPV to be significant predictors of development and progression of nephropathy. 57,58 Finally, in a recent retrospective analysis of a community-based cohort of 114 900 adults with CKD stages 3 to 4, increasing values of visit-to-visit BPV (defined as coefficient of variation, SD, or average real variability) were associated with higher risk of death, incident-treated ESRD, and cardiovascular events.…”
Section: Midterm Bpv (Day-by-day Assessment By Hbpm) Long-term (Visimentioning
confidence: 99%